Development of Ball Tower Model for Learning Top Spin Forehand Strikes in Tennis - Yambedoan, Thadius; Suhartini, Bernadeta; Sulistiyono; Wasa, Carolus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Learning the forehand topspin stroke is essential for students in the Physical Education and Health program at Musamus University, Merauke, as it underpins advanced tennis skills and performance. This study identifies challenges faced by students in mastering this technique, including unbalanced body positions, difficulties in selecting proper racket grips, and limited access to facilities and tools. The research employed a quantitative developmental approach, collecting data from 23 student respondents through a questionnaire focusing on body positioning, racket grip, technique understanding, and facility availability. Descriptive statistical analysis revealed that 75% of students struggled with unbalanced body positions, 70% lacked preparation, and 50% faced concentration issues. Furthermore, 60% reported confusion with racket grip selection, while 80% cited inadequate facilities as a major barrier. These findings highlight the need for targeted interventions, such as improved training programs, enhanced resources, and clearer instructional methods, to address these challenges. This research underscores the importance of addressing these obstacles to optimize student learning outcomes in tennis skill acquisition.